DESIGN, MANUFACTURING AND TESTING OF HYBRID AUV ITB - Fauzi Hanafi, Agung
Ocean is part of the earth that has not been explored by humans. It contains resources that can be utilized for the survival of human life on this earth. The autonomous underwater vehicle called AUV is one of the types of rides that can represent humans in exploring the contents of the oceans. The large area of the ocean that to be explored encourages AUV technology to save energy consumption. On the vehile like AUV, the largest energy consumption is the propulsion system of the vehile. therefore, many people develop a more efficient propulsion system, one of them is a buoyancy engine. Nowdays the vehicle that use buoyancy engine drive system has its own group called underwater glider or commonly refer as glider. To reduce the energy consumption of the AUV drive system, a vehicle is designed by combines the agility of the AUV and the efficient energy consumption of the glider is called as Hybrid AUV ITB. By utilizing thruster from the AUV, the vehicle can move more agile at a certain depth level. Combined with the buoyancy engine mechanism, the vehicle can dive with a smaller energy consumption. In addition, a moving mass mechanism is designed to compensate for the displacement of the center of mass and the center of buoyancy of the vehicle. By adding wings and stabilizers, the vehicle can change the buoyant force acting on the vehicle into a forward movement so that the vehicle can glide mor farther From this research, Hybrid AUV ITB can change buoyancy up to 1,49 kg. By maintaining the vehicle's pitch angle at 7°, the vehicle can reach the smallest glide angle, which is 17,43°. The smaller the gliding angle that is formed, the distance of the vehicle's while performing the gliding maneuver will be further away.